2016
DOI: 10.1002/jobm.201600152
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of extracellular laccase produced byCeriporiopsis subvermisporaand decolorization of triphenylmethane dyes

Abstract: Laccases of white-rot fungi provide a promising future as a tool to be used in the field of biodegradation of synthetic dyes with different chemical structures. The aim of this study was production, characterization, and application of laccases from the white-rot fungus Ceriporiopsis subvermispora ATCC 90467 for decolorization of triphenylmethane dyes that could remain persistent in wastewater. Laccase was purified from a C. subvermispora culture by a four-step method resulting high specific activity of 2,571 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 51 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…Enzymes allow the development of sustainable catalytic processes compared to their chemical counterparts, since they are more specific to target substrates, allow a lower consumption of chemicals, and are natural, renewable, and biodegradable (Datta et al, 2013). For these reasons, enzymes are important catalysts, exhibiting high potential in many industrial applications, such as in the chemical, textile, food, and pharmaceutical industries (Chapman et al, 2018;Rajhans et al, 2021). However, to make these enzymatic processes economically viable, it is crucial to achieve the reuse of the selected biocatalyst while maintaining its catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes allow the development of sustainable catalytic processes compared to their chemical counterparts, since they are more specific to target substrates, allow a lower consumption of chemicals, and are natural, renewable, and biodegradable (Datta et al, 2013). For these reasons, enzymes are important catalysts, exhibiting high potential in many industrial applications, such as in the chemical, textile, food, and pharmaceutical industries (Chapman et al, 2018;Rajhans et al, 2021). However, to make these enzymatic processes economically viable, it is crucial to achieve the reuse of the selected biocatalyst while maintaining its catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method for the production of laccase and other lignocellulolytic enzymes is based on the cultivation of appropriate microbial producer, such as white-rot fungus, on the lignocellulosic material such as wood, straw or hay (Gonzáles et al 2013;Kneževic et al 2013;Chmelová and Ondrejovič 2016). The results of this method are not suitable for the commercial production of target enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that prior upregulation of the required enzymes is the most efficient method for degrading dyes (Ma et al, 2016;Kittl et al, 2012). Microbial degradation of dyes primarily depends on enzymes related to lignin degradation, such as laccase, lignin peroxidase and manganese peroxidase (Grandes-Blanco et al, 2020;Chmelová and Ondrejovic, 2016;Jia et al, 2004;Wang et al, 2016). Pleurotus eryngii, a white-rot fungus, has a high potential to produce various ligninolytic enzymes capable of degrading lignin, cellulose and hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%